Principles of geographical information system for land resources assessment - Burrough, P. A. (Oxford, 1986)
Geographical information systems are being increasingly used by governmental and non-governmental environmental resource and planning agencies to record the characteristics of the earth's spatial resources - land, water, soil, vegetation, people - in digital form. These digital databases are replacing paper maps as data stores because they permit quick, quantitative analysis of complex spatial data and modelling of proposed spatial policies. Technical information about the principles and applications of geographical information systems is spread over a wide range of disciplines, ranging from cartography to spatial statistics to computer science. This book is one of the first to bring these principles together so that environmental scientists of all kinds, from university students to resource managers, can find out the essentials of these new tools and learn how to use them. It includes extensive lists of references, allowing readers to pursue specialist topics further.
Keywords: Land use Data processing